2020
DOI: 10.1186/s40795-020-00351-w
|View full text |Cite
|
Sign up to set email alerts
|

Potential of galled leaves of Goji (Lycium chinense) as functional food

Abstract: Background: Goji (Lycium) is a popular traditional health food, and its fruit and root extracts have been found to possess antioxidant, anti-inflammatory, and hypocholesterolemia-inducing abilities. Goji leaves also contain high amounts of phenolic compounds, similar to its fruit, and their extracts also exhibit several pharmaceutical effects. The induction of galls on Goji leaves reduces their photosynthetic ability and fruit yield, which raise their farming costs, thereby leading to economic loss. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In this study, a significantly higher concentration of chlorogenic acid was detected in the leaves grown in the orchard than in vitro (Table 4). This is in accordance with the results obtained by Chen et al [13], who also confirmed that in goji fruit the concentration of chlorogenic acid is very low in comparison to the leaves. This demonstrates that goji leaves are a valuable source of chlorogenic acid Flavonoids, belonging to polyphenolic compounds, are also commonly found in plants, especially in fruit and vegetables [33].…”
Section: Polyphenolic Compounds and Health Promoting Capacitiessupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, a significantly higher concentration of chlorogenic acid was detected in the leaves grown in the orchard than in vitro (Table 4). This is in accordance with the results obtained by Chen et al [13], who also confirmed that in goji fruit the concentration of chlorogenic acid is very low in comparison to the leaves. This demonstrates that goji leaves are a valuable source of chlorogenic acid Flavonoids, belonging to polyphenolic compounds, are also commonly found in plants, especially in fruit and vegetables [33].…”
Section: Polyphenolic Compounds and Health Promoting Capacitiessupporting
confidence: 93%
“…According to many authors [6,26,31], the antioxidant activity of various plant species (fruit or leaves) may be determined by growing conditions, geographical location, climatic conditions, genotype, fruit maturity, or even the collection methods. Many authors have highlighted that fruit rich in significant amounts of phytochemicals are of great interest to potential consumers [6,13].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The closely related Lycium barbarum and L. chinense solanaceous species are known in Europe and Romania as Goji or Goji berry and their use increased exponentially in the last decades, being promoted as superfruits and functional foods (Wetters et al, 2018). The Goji has been used for millennia in China and neighboring countries for maintaining good health through traditional medicine and cuisine, and the recent attention in western countries is due to the high amounts of functional components, such as sugars, carotenoids, and essential fatty acids from plants (Yossa Nzeuwa et al, 2019, Chen et al, 2020. According to various authors, the genus Lycium includes globally more than 100 (Hummer et al 2012), 80 (Zeng et al, 2014), or 70 species (Mocan et al, 2014) of deciduous or evergreen woody shrubs, but only three species are considered having high commercial value, L. barbarum, L. chinense and L. ruthenicum.…”
Section: Introductionmentioning
confidence: 99%
“…With such a rich biochemical composition, goji fruits are very widely used in pharmacology due to their high anti-cancer (Tang et al, 2012;Cumaoglu et al, 2018), anti-hyperglycemic (Potterat, 2010;Wojdyło et al, 2018), anti-inflammatory (Liu et al, 2015;Wang et al, 2017), anti-aging properties Wojdyło et al, 2018), and antioxidant properties (Illić et al, 2020). Not only do the fruits contain biologically active substances, but also other parts of plants, especially leaves (Chen et al, 2020;Szot et al, 2020). The nutritional properties of Lycium fruits grown in Ukraine have not been investigated.…”
Section: Introductionmentioning
confidence: 99%